Large-scale expansion and characterization of human adult neural crest-derived multipotent stem cells from hair follicle for regenerative medicine applications - Vasyliev, R.G.; Rodnichenko, A.E.; Gubar, O.S.; Zlatska, A.V.; Gordiienko, I.M.; Novikova, S.N.; Zubov, D.O. (Experimental Oncology, 2017)
Aim: The purpose of this work was to obtain, multiply and characterize the adult neural crest-derived multipotent stem cells from human hair follicle for their further clinical use. Materials and Methods: Adult neural crest-derived multipotent stem cells were obtained from human hair follicle by explant method and were expanded at large-scale up to a clinically significant number. The resulted cell cultures were examined by flow cytometry and immunocytochemical analysis. Their clonogenic potential, ability to self-renewal and directed multilineage differentiation were also investigated. Results: Cell cultures were obtained from explants of adult human hair follicles. Resulted cells according to morphological, phenotypic and functional criteria satisfied the definition of neural crest-derived multipotent stem cells. They had the phenotype Sox2⁺Sox10⁺Nestin⁺CD73⁺CD90⁺CD105⁺CD140a⁺CD 140b⁺CD146⁺CD166⁺CD271⁺CD349⁺ CD34⁻CD45⁻CD56⁻HLA⁻DR⁻, showed high clonogenic potential, ability to self-renewal and directed differentiation into the main derivatives of the neural crest: neurons, Schwann cells, adipocytes and osteoblasts. Conclusion: The possibility of a large-scale expansion of adult neural crest-derived multipotent stem cells up to 40–200·106 cells from minimal number of hair follicles with retention of their phenotype and functional properties are the significant step towards their translation into the clinical practice.